MICRO AND SMALL ENTERPRISES FINANCING MODEL THROUGH THE REVOLVING FUND MANAGEMENT INSTITUTION IN INDONESIA: AHP APPROACH - Taufik Nugroho; Aam Slamet Rusydiana; Naelati Tubastuvi (IJIBE (International Journal of Islamic Business Ethics), 2018)
The government established a Revolving Fund Management Institution (LPDB) which aims to help capitalize MSMEs by providing loan and financing assistance as needed. This study attempts to analyze effective MSME financing strategies to improve LPDB’s performance using the Analytic Hierarchy Process approach. The results show thatfrom the perspective ofgoals development, an increase in the workforce is considered more priority than a reduction in poverty and inequality. Meanwhile, from the perspective of the criteria for developing LPDB in Indonesia, the success of utilization is the priority compared to other criteria. From an alternative side, the form of a cooperative or Islamic cooperative is preferred over other forms.Keywords: LPDB Sharia, Small medium enterprises, Analytic Hierarchy Process